Good governance in Central and Eastern Europe: The European Union as an anchor for reform - Herman Hoen (Economic and Environmental Studies (E&ES), 2013)
In this article, it is argued that the economic and political transformation in Central and Eastern European countries towards the end of the twentieth century towards a market economy were irreversible and path dependent. The author discusses the importance of this issue for the success of transformation policies, as well as the significance of the role of the European Union for supporting good governance as a condition for successful transformation.
Keywords: 330; good governance; Central and Eastern Europe; European Union; economic transformation; path dependency